2011
DOI: 10.1074/jbc.m110.210765
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer/Testis Antigen Prostate-associated Gene 4 (PAGE4) Is a Highly Intrinsically Disordered Protein

Abstract: The cancer/testis antigens (CTAs) are an important group of heterogeneous proteins that are predominantly expressed in the testis in the normal human adult but are aberrantly expressed in several types of cancers. Prostate-associated gene 4 (PAGE4) is a member of the CT-X family of CTAs that in addition to testis, is highly expressed in the fetal prostate, and may also play an important role both in benign and malignant prostate diseases. However, the function of this gene remains poorly understood. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 39 publications
1
76
0
Order By: Relevance
“…However, the PAGE4 protein is up-regulated in both symptomatic benign prostatic hyperplasia, which is related to prostate cancer (13), and in prostate cancer itself (12,15,16), indicating a potential role for PAGE4 in disease pathology. Consistent with this hypothesis, knocking down PAGE4 expression results in cell death, whereas its overexpression leads to a growth advantage of prostate cancer cells (17).…”
supporting
confidence: 66%
“…However, the PAGE4 protein is up-regulated in both symptomatic benign prostatic hyperplasia, which is related to prostate cancer (13), and in prostate cancer itself (12,15,16), indicating a potential role for PAGE4 in disease pathology. Consistent with this hypothesis, knocking down PAGE4 expression results in cell death, whereas its overexpression leads to a growth advantage of prostate cancer cells (17).…”
supporting
confidence: 66%
“…48 NMR analysis revealed that an important regulator of proliferation and apoptosis, cAMPresponsive (CRE)-binding (CREB) protein (CBP), contains an intrinsically disordered ACTR-binding domain (residues 2059-2117) that completely folds upon binding. 49 Combined experimental and computational analysis revealed that N-and C-terminal regions of the human Nogo proteins 50 and C-terminal domain of a mitochondrial pro-apoptotic protein ARTS 51 are typical IDPRs, and that the prostate apoptosis response factor-4 (PAR-4), 52 prostate-associated gene 4 (PAGE4) protein, 53 and important oncoprotein c-Myc 54 are mostly disordered apoptosis-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…PAGE4 is a cancer/testis antigen that is intrinsically disordered (>95%) (29) and is remarkably prostate-specific in the human male (30). It has the hallmarks of a protooncogene, with important roles in development and differentiation.…”
Section: Significancementioning
confidence: 99%
“…33). However, PAGE4 protein expression is elevated in prostate cancer (PCa) (31,(34)(35)(36), where it is upregulated in response to a variety of stress factors (29,31). PAGE4 is phosphorylated at S9 and T51 by HomeodomainInteracting Protein Kinase 1 (HIPK1), a component of the cellular stress-response pathway, and functions as a strong potentiator of the oncoprotein c-Jun (32,37).…”
Section: Significancementioning
confidence: 99%